Hypertension: evolving from standardized to individualized care. Issue 7 (July 2020) - Alderman, Michael H.; Blumenfeld, Jon D.
Abstract : N/A: The hypertension paradigm has contributed to a dramatic reduction in CVD mortality. This has been achieved by applying average results of population studies to identify a target population and design a common intervention to achieve a BP goal. Progressive lowering of the BP threshold has expanded the fraction of persons at risk who have access to treatment. Meanwhile, falling risk reduces potential benefit, while treatment-induced adverse events increase – making further expansion of the treatment pool no longer tenable. Still, CVD remains the leading cause of death. Fortunately, new science reveals opportunities to enhance CVD prevention when BP management is based upon individual characteristics. Treatment can be directed at those most likely to benefit, while sparing others the hazards of unnecessary therapy. Treatment can be designed to achieve a variety of physiological objectives that influence cardiovascular outcomes. This new strategy should improve both the efficacy and efficiency of BP-related CVD prevention.